Development of and Clinical Experience with a New TV Monitoring System in Electronic Endoscopy - Okano, H.; Kodama, T.; Takino, T. (Endoscopy, 1988)
We developed a bi-plane TV monitoring system using a TV endoscope (Electronic endoscope manufactured by Toshiba-Machida, Tokyo, Japan) that permits simultaneous display of real-time and prerecorded images. Various findings of the two examinations can be precisely compared using this system, and a detailed evaluation of the progress of peptic ulcers obtained. In addition, the effects of various endoscopic therapies can be accurately evaluated. In endoscopic injection sclerotherapy of esophageal varices, now varices (or recurrent varices) were differentiated. In laser therapy for early gastric cancer, precise delimitation of the lesion for radiation was possible, and the therapeutic effects were more accurately evaluated. These results show the diagnostic as well as therapeutic usefulness of this system. Furthermore, for the examination of the lower digestive tract, X-ray images were incorporated into this system. This is a useful modality for diagnostic and therapeutic procedures in colonic disease.
Keywords: Electronic endoscopy; Bi-plane TV monitoring system